Novel and Promising Strategies for Therapy of Post-Transplant Chronic GVHD - Irina Kostareva; Kirill Kirgizov; Elena Machneva; Nadezhda Ustyuzhanina; Nikolay Nifantiev; Yulia Skvortsova; Irina Shubina; Vera Reshetnikova; Timur Valiev; Svetlana Varfolomeeva; Mikhail Kiselevskiy (MDPI AG, 2022)
Despite the achievements that have increased viability after the transplantation of allogeneic hematopoietic stem cells (aHSCT), chronic graft-versus-host disease (cGVHD) remains the main cause of late complications and post-transplant deaths. At the moment, therapy alternatives demonstrate limited effectiveness in steroid-refractory illness; in addition, we have no reliable data on the mechanism of this condition. The lack of drugs of choice for the treatment of GVHD underscores the significance of the design of new therapies. Improved understanding of the mechanism of chronic GVHD has secured new therapy goals, and organized diagnostic recommendations and the development of medical tests have ensured a general language and routes for studies in this field. These factors, combined with the rapid development of pharmacology, have helped speed up the search of medicines and medical studies regarding chronic GVHD. At present, we can hope for success in curing this formidable complication. This review summarizes the latest clinical developments in new treatments for chronic GVHD.